The effects of aquatic exercise on body composition, physical fitness, and vascular compliance of obese elementary students - Lee, Bo-Ae; Oh, Deuk-Ja (Journal of exercise rehabilitation, 2014)
The purpose of this study was to investigate the effects of aquatic exer-cise on body composition, physical fitness, and vascular compliance of obese elementary school students. For the purpose of this study, 20 obese elementary students were selected as subjects. The subjects were then divided into two groups: the swimming group (n=10) and the control group (n=10). The subjects were asked to exercise for 60 min-utes a day, 3 times a week for 12 weeks with an exercise intensity of 50-70% HRmax. The following results were achieved: first, in terms of body composition, both body fat percentage and fat-free mass showed sig-nificant differences within the swimming group. There were also signifi-cant differences again in the posttest of difference between the two groups. Second, in terms of changes in physical fitness, there were, again, no significant changes in muscular strength between the two groups. However, muscular endurance, flexibility, and cardiopulmonary endurance showed significant differences in the swimming group’s test for difference within groups. Significant differences in both groups for the posttest of differences between groups were also seen. Third, in terms of vascular compliance, there was a significant increase in the right leg for the swimming groups’ test of difference within groups, as well as in the posttest of difference between groups.